Future trends in CAD – from the perspective of automotive industry. Issue 6 (19th September 2017) - Hirz, Mario; Rossbacher, Patrick; Gulanová, Jana
ABSTRACT: Computer-aided design (CAD) plays a central role in automotive development. 3D-CAD models not only provide geometry information, but also serve as a basis for configuration of modules and systems, as well as for different simulation and verification processes. Product assemblies within CAD-platforms include structure-related information, are used for digital mock-up (DMU) investigations and provide lots of data for production and manufacturing engineering. Since first CAD systems have been applied in automotive industry in the 1980s, design software has been developed steadily, so that today's CAD programs are able to provide far-reaching possibilities for integrated product development. The present paper includes an introduction and evaluation of existing and upcoming technologies for their use in future CAD programs and discusses different scenarios of implementation into automotive development. Vehicle architects, design engineers, project managers, IT-administrators for CAD, stylists as well as styling engineers have contributed to a survey at automotive manufacturer and supplier. The results of this survey are brought into this paper to discuss the future role of CAD in the development of new cars and to define requirements for the next generation of CAD software. GRAPHICAL ABSTRACT: